Moving towards the ecological intensification of tree plantations. (July 2022) - Gómez-González, Susana; Paniw, Maria; Blanco-Pastor, José Luis; García-Cervigón, Ana I.; Godoy, Oscar; Herrera, José M.; Lara, Antonio; Miranda, Alejandro; Ojeda, Fernando; Ochoa-Hueso, Raúl
Abstract : The growing demand for timber and the boom in massive tree-planting programs could mean the spreading of mismanaged tree plantations worldwide. Here, we apply the concept of ecological intensification to forestry systems as a viable biodiversity-focused strategy that could be critical to develop productive, yet sustainable, tree plantations. Tree plantations can be highly productive if tree species are properly combined to complement their ecological functions. Simultaneously considering soil biodiversity and animal-mediated biocontrol will be critical to minimize the reliance on external inputs. Integrating genetic, functional, and demographic diversity across heterogeneous landscapes should improve resilience under climate change. Designing ecologically intensified plantations will mean breaking the timber productivity versus conservation dichotomy and assuring the maintenance of key ecosystem services at safe levels. Highlights: Current biodiversity and climate crises are forcing society to adopt new forms of forestry management that reconcile conservation, environmental health, and productivity. Ecological intensification, a pathway to improve yield productivity by increasing biodiversity and ecological functions, can and must be applied to forestry as a way to achieve sustainable and resilient tree plantations. Ecological intensification differs from other initiatives of sustainable management in that biodiversity is the vehicle to boost productivity and is not incompatible with protected areas. An appropriate management to restore and/or enhance both above- and below-ground diversity will increase not only productivity in the short term but also the long-term viability of tree plantations in a climate- change scenario.